2018
DOI: 10.1177/2320206818812538
|View full text |Cite
|
Sign up to set email alerts
|

Insights about Dental Ergonomics among Dental Students: The Need of the Hour to Recommend Dental Ergonomics in Academic Curriculum

Abstract: Aims and Objectives: To assess the perception, practice, and attitude about dental ergonomics among dental students in Chennai. Materials and Methods:The study was carried out among 148 dental students in Chennai, Tamil Nadu, using a selfmade validated closed-ended questionnaire.Results: Among 148 dental students, 75 (50.6%) were undergraduate and 73 (49.4%) were postgraduate students. Of the study population, 38 (25.67%) had listed their general health problems which they thought were related to their profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Still, they did not practice it as much as required, which resulted in body pains, increased musculoskeletal stress, and lack of efficient performance. 17,25 Hence, it is very crucial to conduct studies that gauge the KAP of fresh graduates to save them from future health issues by introducing ways to facilitate the inclusion of ergonomic principles into their curriculum during their clinical years. 26 In many studies, it was recommended, and students willingly agreed to the inclusion of ergonomics in their academic curriculum and to attend workshops to further enhance their skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, they did not practice it as much as required, which resulted in body pains, increased musculoskeletal stress, and lack of efficient performance. 17,25 Hence, it is very crucial to conduct studies that gauge the KAP of fresh graduates to save them from future health issues by introducing ways to facilitate the inclusion of ergonomic principles into their curriculum during their clinical years. 26 In many studies, it was recommended, and students willingly agreed to the inclusion of ergonomics in their academic curriculum and to attend workshops to further enhance their skills.…”
Section: Discussionmentioning
confidence: 99%
“…26 In many studies, it was recommended, and students willingly agreed to the inclusion of ergonomics in their academic curriculum and to attend workshops to further enhance their skills. [22][23][24][25][26] With this kind of positive attitude, it will be easier to incorporate ergonomics in routine dental practice, which can also increase awareness of MSDs. This requires significant effort and consistency in the evaluation of the dental education program and implementation of policies at all levels.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study was conducted among 25 dental practitioners to estimate the sample size and to check the feasibility of the study. The sample size was calculated with 80% statistical power, α = 0.05, 95% confidence interval, 10% margin of error (E) and knowledge regarding dental ergonomics (67%) 6 , using Gpower software (Version 3.1.9.7). The sample size was estimated to be about 200 participants, which included postgraduates, staff attending the institution and private practitioners.…”
Section: Methodsmentioning
confidence: 99%
“…5 While performing a treatment; dentists should work meticulously, under conditions where access to the oral cavity is very arduous on an anxious patient which makes the dentist work in strenuous positions with tense muscles further progressing to the development of MSDs. 6 Lietz et al (2018) stated that the prevalence of musculoskeletal disease and pain among dental professionals (dentists, dental hygienists and dental students) vary from 10.8% to 97.9% and found that the neck is the most affected body region since 58.5% of dentists complained about neck pain in the last 12 months. The lower back represented the second most affected body region reported by 56.4% of dentists, followed by shoulder pain (43.1%) and pain in the upper back (41.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Essential ergonomics education is seldom embraced in dental schools [ 14 ]. However, it would be better for future dental graduates to include dental ergonomics in the academic curriculum [ 15 ].…”
Section: Introductionmentioning
confidence: 99%